2008
DOI: 10.1002/chem.200800880
|View full text |Cite
|
Sign up to set email alerts
|

Specific Methyl Group Protonation for the Measurement of Pharmacophore‐Specific Interligand NOE Interactions

Abstract: In the recent decades NMR spectroscopy has emerged as a powerful tool in the drug-discovery field. Several NMRbased methods have proved beneficial for the optimization of low-molecular-weight lead structures. Among those, techniques relying on the nuclear Overhauser effect (NOE) can provide information on pharmacophores at atomic resolution. The transferred-NOEs (tr-NOEs) [1] allow access to the bioactive conformation of ligands and can also be applied as a screening tool to identify the interaction of a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…In recent decades, various methods have been developed in order to derive protein-ligand complex structures faster than with the classical NMR structure calculation protocol, but these methods mostly rely on a preliminary docking step rather than on experimentally driven calculations. Moreover, sometimes partial resonance assignments of the receptor are required [39][40][41][42][43][44][45]47,49,72]. A complex structure calculation method that is based on defined and accurate NOEs [78][79][80] but also bypasses the long and tedious protein assignment step was missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, various methods have been developed in order to derive protein-ligand complex structures faster than with the classical NMR structure calculation protocol, but these methods mostly rely on a preliminary docking step rather than on experimentally driven calculations. Moreover, sometimes partial resonance assignments of the receptor are required [39][40][41][42][43][44][45]47,49,72]. A complex structure calculation method that is based on defined and accurate NOEs [78][79][80] but also bypasses the long and tedious protein assignment step was missing.…”
Section: Discussionmentioning
confidence: 99%
“…CORCEMA [46,68,69] and INPHARMA [48,67,72,73] are methods that back predict intra-ligand, intra-protein and protein-ligand NOEs or spin diffusion using the full relaxation matrix formalism. They are powerful tools that can also handle systems undergoing multistate conformational exchange and chemical exchange between the free and bound states.…”
Section: Nmr 2 Versus Other Methods For Rapid Structure Calculations mentioning
confidence: 99%
“…However, we have recently demonstrated that the INPHARMA approach is much more powerful and allows in favorable cases the de novo description of the binding mode of both L 1 and L 2 [11,12]. In this work we have shown that the methodology is precise enough to unambiguously select one docking mode per ligand and accurate enough to select the correct docking mode, as compared to the crystal structures available for the investigated test cases [12].…”
Section: Introductionmentioning
confidence: 90%
“…To overcome this problem, we developed the INPHARMA methodology (Interligand Noes for PHARmacophore MApping) that allows mapping the structure of the binding pocket of a macromolecule on the NMR resonances of two competitively binding ligands [11][12][13][14]. The method is based on the observation of interligand, spin-diffusion mediated, transferred-NOE data, between two ligands L 1 and L 2 , binding competitively and weakly to a macromolecular receptor T (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…O INPHARMA permite observar a orientação de ligantes no sítio do receptor, e para isso, são utilizados dois ligantes (L 1 e L 2 ) competitivos pelo mesmo sítio e com baixa ou média afinidade pelo receptor (Orts, 2008;.…”
Section: = K B T/funclassified